Meningioangiomatosis: A Case Report and Literature Review Emphasizing Diverse Appearance on Different Imaging Modalities. (9th October 2011) - Kashlan, Osama N.; LaBorde, David V.; Davison, LaKesha; Saindane, Amit M.; Brat, Daniel; Hudgins, Patricia A.; Gross, Robert E.
Abstract : Purpose . Meningioangiomatosis (MA) is a rare, benign lesion that commonly mimics other intracranial malformations in clinical presentation and appearance on imaging. The case presented and the literature review performed highlight the importance of combining MRI and CT results to better characterize intracranial lesions and including MA on the list of differential diagnoses of patients presenting with seizures. Methods . The case described is of a 19-year-old male with a 10-year history of worsening seizures refractory to multiple drug regimens. MRI revealed an atypical vascular malformation. The patient underwent surgical resection of the epileptogenic cortex. Results . Although the radiologic impression of the lesion was a vascular malformation, pathological examination revealed MA. A literature search performed highlights the variability of the appearance of MA on CT and MRI and suggests the utility of the T2 GRE sequence in illustrating the presence of calcification and, in a lesion with other characteristic features, the diagnosis of MA. Conclusion . MA can be a difficult diagnosis to make based on imaging findings alone. However, in a patient with a characteristic history and presentation, the presence of a calcified mass on CT and MRI brain susceptibility artifact on a T2 GRE sequence may suggest MA.